Ảnh hưởng của siêu cá nhân hóa và tích hợp kênh đến ý định tiếp tục sử dụng hợp kênh trong lựa chọn khách sạn: Vai trò điều tiết của danh tính di động - Trần Xuân, Quỳnh; Nguyễn Thị Thanh, Mai (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to analyze the impact of hyper-personalization and channel integration on omni-channel satisfaction, usage habit, and the intention to continue using omni-channel hotel booking in Vietnam, while also exploring the moderating role of mobile identity. Data were collected through an online survey of 401 users who had recently experienced omni-channel hotel booking. The results reveal that hyper-personalization and channel integration both have a positive effect on omni-channel satisfaction and usage habit, which in turn influence the intention to continue using. Mobile identity was found to have a significant moderating effect on omni-channel satisfaction. The study also offers several practical implications for hotels in Vietnam in developing omni-channel customer engagement strategies and personalized marketing approaches.
Keywords: Mobile customer identity; Omnichannel retailing; Channel integration; Hyper-personalization